2012
DOI: 10.1111/j.1476-5381.2012.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant‐like effects of ginsenoside Rg1 are due to activation of the BDNF signalling pathway and neurogenesis in the hippocampus

Abstract: BACKGROUND AND PURPOSEGinsenoside Rg1 (Rg1) is one of the major bioactive ingredients of Panax ginseng with little toxicity and has been shown to have neuroprotective effects. In this study, we investigated the antidepressant-like effect of Rg1 in models of depression in mice. EXPERIMENTAL APPROACHThe effects of Rg1 were assessed in the forced swimming test (FST) and tail suspension test (TST) in mice. Rg1 was also investigated in the chronic mild stress (CMS) mouse model of depression with imipramine as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(145 citation statements)
references
References 84 publications
4
138
2
Order By: Relevance
“…Finally, the prevailing perception in the literature, suggests FST to be a proper test to show neurogenesis-dependence of antidepressant efficacy. Several groups described X-irradiation to block antidepressant effects using FST (e.g., Zhu et al, 2010;Garza et al, 2012) while correlative observations linking antidepressant treatment effects in FST and adult hippocampal neurogenesis have been reported numerous times (Liu et al, 2008;Silva et al, 2008;Schmidt and Duman, 2010;Wainwright et al, 2011;Wang et al, 2011;Jiang et al, 2012;Lin and Wang, 2014;Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the prevailing perception in the literature, suggests FST to be a proper test to show neurogenesis-dependence of antidepressant efficacy. Several groups described X-irradiation to block antidepressant effects using FST (e.g., Zhu et al, 2010;Garza et al, 2012) while correlative observations linking antidepressant treatment effects in FST and adult hippocampal neurogenesis have been reported numerous times (Liu et al, 2008;Silva et al, 2008;Schmidt and Duman, 2010;Wainwright et al, 2011;Wang et al, 2011;Jiang et al, 2012;Lin and Wang, 2014;Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2,26) The mice were placed individually in the center of a wooden box (100×100×40 cm) with the floor divided into 25 (5×5 cm) squares and allowed to act at liberty. The apparatus was covered with a black surface and illuminated with a red bulb (50 W).…”
Section: Methodsmentioning
confidence: 99%
“…2,36) Thus, the possible antidepressant effects of AST were first examined in the FST. AST (10, 20, 40 mg/kg) was given i.p.…”
Section: Ast Treatment Produces No Effect On Spontaneous Locomotor Acmentioning
confidence: 99%
“…Jiang et al (30) reported the effect of Rg1 in a mouse model of chronic mild stress (CMS). Rg1 has antidepressant-like effect in the forced swim test and tail suspension test, and it could up-regulate the BDNF signaling pathway of the hippocampus and down-regulate the level of plasma corticosterone.…”
Section: Action Of Anti-depressionmentioning
confidence: 99%